WE4.4 Robotic versus laparoscopic splenectomy in management of non-traumatic splenic pathologies: a systematic review and meta-analysis. (9th August 2022) - Hajibandeh, Shahin; Hajibandeh, Shahab; Bhattacharya, Pratik; Phelan, Liam; Patel, Ishaan
Abstract: Aims: We aimed to evaluate comparative outcomes of robotic and laparoscopic splenectomy in patients with non-traumatic splenic pathologies. Methods: A systematic search of electronic databases and bibliographic reference lists were conducted and a combination of free text and controlled vocabulary search adapted to thesaurus headings, search operators and limits in electronic databases were applied. Intra-operative and post-operative complications, wound infection, haematoma, conversion to open procedure, return to theatre, volume of blood loss, procedure time, and length of hospital stay were the evaluated outcome parameters. Results: Eight comparative studies reporting a total of 560 patients comparing outcomes of robotic (n=202) and laparoscopic (n=258) splenectomies were included. The robotic approach was associated with significantly lower volume of blood loss (MD:-82.53 mls, 95% CI-161.91–-3.16, p=0.04) compared to the laparoscopic approach. There was no significant difference in intra-operative complications (OR:0.68, 95% CI 0.21–2.01, p=0.51), post-operative complications (OR:0.91, 95% CI 0.40–2.06, p=0.82), wound infection (RD:-0.01, 95% CI -0.04–0.03, p=0.78), haematoma (OR:0.40, 95% CI 0.04–4.03, p=0.44), conversion to open (OR:0.63; 95% CI, 0.24–1.70, P=0.36), return to theatre (RD:-0.04, 95% CI -0.09–0.02, p=0.16), procedure time (MD: 3.63; 95% CI, -16.99–24.25, P=0.73) and length of hospital stay (MD:-0.21; 95% CI, -1.17–0.75, P=0.67) between two groups. Conclusions: Robotic and laparoscopic splenectomy seem to have comparable perioperative outcomes with similar rate of conversion to an open procedure, procedure time and length of hospital stay. The former may potentially reduce the volume of intra-operative blood loss. Future higher level research is required to evaluate the cost-effectiveness and clinical outcomes